2015
DOI: 10.5114/kitp.2015.50562
|View full text |Cite
|
Sign up to set email alerts
|

THORACIC SURGERY Results of surgical treatment of primary lung cancer with synchronous brain metastases

Abstract: IntroductionThe surgical treatment of non-small cell lung cancer (NSCLC) with synchronous brain matastases is more effective than other therapeutic options, but this management is still controversial.The aim of the studyThe aim of the study was to evaluate the survival of patients after pulmonary resection NSCLC preceded by resection of brain metastases.Material and methodsFrom 2007 to 2012, 645 patients underwent pulmonary resection for NSCLC at our department. In 25 of them (3.87%) thoracic surgery was prece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This latter aspect leads criticisms due to sometimes discordant reports. Bella et al ,23 in a retrospective study involving 645 NSCLC patients and 25 of those with M1-brain disease, reported no significant differences in prognosis when histotype is considered (p=0.57).…”
Section: Discussionmentioning
confidence: 94%
“…This latter aspect leads criticisms due to sometimes discordant reports. Bella et al ,23 in a retrospective study involving 645 NSCLC patients and 25 of those with M1-brain disease, reported no significant differences in prognosis when histotype is considered (p=0.57).…”
Section: Discussionmentioning
confidence: 94%
“…There are several studies suggesting mediastinoscopy to meet this goal. [18,19] Therefore, we performed standard cervical mediastinoscopy in all patients to evaluate the status of the mediastinal lymph nodes before pulmonary resection. We completed the lung resections, when the frozen-section examinations of lymph nodes resulted negative.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical excision has been considered an effective approach for managing BM resulting from NSCLC, the median survival time for patients who experience such a disease progression is less than 3 months ( 24 ). As a standard treatment for BM caused by NSCLC, WBRT has improved the median survival time to approximately 5 months ( 25 ).…”
Section: Discussionmentioning
confidence: 99%